Strategies for resuming higher education in healthcare in relation to COVID-19 - Oliveira, Zulmerinda Meira (2020)
Objective: To reflect on the adoption of strategies to be implemented by Higher Educational Institutions that offer courses in the healthcare field to continue their academic activities during the COVID-19 pandemic, focusing on the physical and mental health of their teachers and students. Methods: It is a reflective theoretical study structured in three thematic axes, whose bibliographic survey covered books, official documents from the Ministry of Health of Brazil, national and international scientific articles from the databases of PUBMED/MEDLINE, Web of Science, LILACS and SciELO. The selection was conducted using combinations of keywords related to the issue: “COVID-19”, “online teaching”, “biosafety”, “online learning”, “stress”, “integrative and complementary healthcare practices”. Results: The first axis highlights the adoption of virtual strategies to avoid agglomerations and the risk of contamination by COVID-19; the second, the use of biosafety measures to carry out on-site academic activities; and the third, actions to cope with the emotional stress experienced by teachers and students in this context. Conclusions: It is essential to adopt pedagogical strategies in an attempt to find creative and responsible solutions for Higher Educational Institutions in Health in order to minimize teaching-learning weakening and avoid damage to the physical and mental health of those who are protagonists of this process.